Rhodotorula minuta-mediated bioreduction of 1,2-diketones - Monsalve, Leandro Nicolas (2010)
The reduction of cyclic and acyclic 1,2-diketones was investigated by employing whole cells of the yeast Rhodotorula minuta as biocatalyst. The reactions showed a variable degree of regio- and enantioselectivity depending on the nature of the substrate. In the case of cyclic diketones, the reduction afforded a mixture of diastereomeric diols only. The reduction of acyclic diketones allowed production of both the hydroxy ketone and the diol, in a two-step reaction. The first step was highly regio- and stereoselective, affording the hydroxy ketone of (S)-configuration with high enantiomeric excess. After longer reaction times the corresponding (S,S)-diols were obtained in high yield and diastereomeric excess. © 2010 Informa UK Ltd.